Studi Potensi Pirazolin Tersubstitusi 1-N dari Thiosemicarbazone sebagai Agen Antiamuba melalui Uji In Silico - La Kilo, Akram; Aman, La Ode; Sabihi, Ismail; La Kilo, Jafar (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
This Research aims to study Quantitative Structure-Activity Relationship (QSAR) of pyrazoline analogues, designing the new potential compounds as antiamoebic and study the interactions between the new compunds and the drugs target by molecular docking approach. This research was a theoritical research using computational chemistry method. The object of research was 21 novel of 1-N-substituted pyrazoline analogues of thiosemicarbazones with their antiamoebic biological activity. The data of research was obtained from quantum chemistry calculation and statistically analysis using Multiple Linear Regression (MLR). The resulting QSAR equation was Log IC50 = 0.869 + (0.081 x TPSA) + (0.018 x HF) + (0.527 x E-HOMO) + (3.378 x E-LUMO) + (-16.938 x Glob) + (0.234 x LogP), with statistic parameters of n = 21; R2 = 0.933; SEE = 0.14558; FHitung/FTabel = 8.607; PRESS = 0.491. This equation was used as a basic for designing and predicting the new antiamoebic compounds of pyrazoline analogues. The design of new compound of two lead compounds with the Topliss resulted 5 of 18 new compounds having theoretical better activity than the lead compound. Molecular docking study indicated that all of the best compounds have ability to bind to drug target macromolecule.